THE EFFECT OF CORPORATE GOVERNANCE ON FINANCIAL STATEMENT FRAUD WITH FIRM SIZE AS A MODERATING VARIABLE - Mega Duarti; Radhi Abdul Halim (PT. Radja Intercontinental Publishing, 2026)
This study aims to provide empirical evidence on the effect of corporate governance—proxied by the board of commissioners, audit committee, and institutional ownership—on financial statement fraud, with firm size as a moderating variable. The population characteristics of mining companies listed on the Indonesia Stock Exchange (IDX) for the period 2021–2024. Using purposive sampling, 58 companies were selected with a total of 285 observations. The data were analyzed using panel data regression with the Fixed Effect Model (FEM) and Moderated Regression Analysis (MRA). Financial statement fraud was measured using the Beneish M-Score. The results show that: (1) the board of commissioners does not significantly affect financial statement fraud; (2) the audit committee does not significantly affect financial statement fraud; (3) institutional ownership has a positive and significant effect on financial statement fraud; (4) firm size strengthens the relationship between the board of commissioners, audit committee, and institutional ownership with financial statement fraud. The R² value of 98.51% indicates the model's high explanatory power.